High-capacity fast-charging graphite negative electrode material, and preparation method and use thereof
Patent Information
- Application Number
- CN202210628548.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-06
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-06-06
AI Technical Summary
现有石墨负极材料在以石油焦生焦为原料时,存在团聚现象,导致倍率性能和容量不足,且生产效率低的问题。
By adding calcined coke to raw petroleum coke and performing dynamic sintering with stirring to avoid agglomeration, combined with pitch granulation and graphitization treatment, a high-capacity, high-density graphite anode material is formed.
While ensuring the scaling performance, the material's capacity and compaction density were increased, production time was shortened, and production efficiency was improved.
Smart Images

Figure CN117239122B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery material technology, specifically relating to a high-capacity fast-charging graphite anode material, its preparation method, and its applications. Background Technology
[0002] Graphite anode materials have the advantages of high capacity and compaction density, good cycle performance, mature preparation technology and low manufacturing cost, making them the mainstream commercial anode materials for lithium-ion batteries. However, as the consumer electronics and power battery fields place increasingly higher demands on fast charging, there is a general desire to improve rate capability under room temperature and low temperature conditions. This means that graphite anode materials must undergo special design and processing to meet the rate requirements.
[0003] CN105024043A discloses a fast-charging graphite lithium-ion battery anode material and its preparation method. The method involves mixing, kneading, and graphitizing natural graphite and asphalt at high temperature to obtain a composite graphite material with a secondary particle structure. Although natural graphite is chosen as the raw material, its capacity is easy to guarantee, but it cannot meet the requirements for high-rate charging.
[0004] Artificial graphite anode materials use petroleum coke as raw material, which is generally composed of small particles, with particles smaller than 0.63mm accounting for 40% to 80%. Due to the high volatile content and large proportion of small particles in the raw material, agglomeration occurs during low-temperature calcination. This leads to uneven heating between the inner and outer layers of the agglomerates. Although the material can be deagglomerated during crushing after low-temperature calcination, the agglomerates are not fully calcined, thus affecting the graphite's capacity, compaction, and other properties. While extending the calcination time, reaction temperature, and stirring speed of the calcination equipment can solve this problem, it will affect the production capacity and energy consumption of this process.
[0005] CN111628170A discloses a porous secondary particle anode material for lithium-ion batteries and its preparation method. The method involves preparing raw petroleum coke and low-temperature plastic pitch into powders, then heat-treating the raw petroleum coke powder in a CO2 atmosphere to form porous petroleum coke. The porous petroleum coke and low-temperature plastic pitch powder are uniformly mixed and added to a high-temperature autoclave for composite granulation at 250–300°C to obtain secondary particles. These secondary particles are then added to a cooling autoclave, where they are simultaneously cooled and oxidized to solidify. Once cooled to room temperature, the secondary particles are discharged to obtain the anode precursor. Finally, the anode precursor is graded, graphitized, sieved, demagnetized, and packaged. However, the method described in this literature suffers from agglomeration during the calcination of raw petroleum coke, leading to a decrease in calcination capacity and affecting the rate performance of the final graphite product.
[0006] Therefore, how to improve the rate performance of graphite anode materials made from petroleum coke raw materials while ensuring their high capacity and compaction density is an urgent technical problem to be solved. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a high-capacity, fast-charging graphite anode material, its preparation method, and its applications. The graphite anode material provided by this invention, by adding calcined coke to raw petroleum coke and then sintering it, effectively avoids the agglomeration of raw coke during sintering, resulting in more complete and uniform sintering. This shortens the sintering time, effectively increases sintering capacity, and improves the material's capacity and compaction density while minimizing the rate performance loss of the graphitized petroleum coke raw coke.
[0008] To achieve this objective, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a graphite anode material, which is obtained by sintering raw petroleum coke and calcined coke, wherein the particle size of the calcined coke is less than or equal to the particle size of the raw petroleum coke.
[0010] In this invention, the raw coke and calcined coke are homologous materials (raw coke: the product obtained by separating light and heavy oils from crude oil through distillation, and then converting the heavy oils through delayed coking; calcined coke: the product obtained by calcining raw coke (1000-1300℃)).
[0011] The graphite anode material provided by this invention, by adding calcined coke to the base of petroleum coke and then sintering it, effectively avoids the agglomeration of the raw coke during the sintering process, and allows for more complete and uniform sintering (allowing the raw coke raw material to be fully heated and its structure to undergo a complete transformation). Compared with the raw coke product, the artificial graphite product obtained from this intermediate coke can improve the material's capacity and compaction density while ensuring a smaller loss in its rate performance, and can also shorten the sintering time, effectively increasing sintering capacity and reducing the material's production cost.
[0012] In this invention, the particle size of the calcined coke is less than or equal to the particle size of the raw petroleum coke, which can effectively play an isolation role. However, if the particle size is too large, it is also easy to cause the raw coke to agglomerate, thereby affecting the capacity and compaction density of the graphite anode material.
[0013] In this invention, the intermediate coke obtained by sintering raw petroleum coke and calcined coke is a transitional structure between raw coke and calcined coke. The fibrous structure in the intermediate coke is further developed, but it still maintains a high degree of isotropy and has not fully developed into a long and fine fiber structure. If the intermediate coke is not obtained by sintering raw petroleum coke and calcined coke, it is difficult to improve the corresponding material capacity and compaction density. If the raw petroleum coke is sintered alone without adding calcined coke, agglomeration will occur during the sintering process, affecting the consistency of the raw materials and ultimately affecting the material capacity, compaction, and ratio.
[0014] Preferably, based on the total mass of the raw petroleum coke and the calcined coke as 100%, the mass of the calcined coke is ≥5% and <10%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, and 9.5%.
[0015] In this invention, if too much calcined coke is added (≥10%), it will seriously affect the rate performance of the material, while if too little calcined coke is added (<5%), it will lead to agglomeration and poor consistency of raw materials during sintering.
[0016] Preferably, the raw materials for the graphite anode material further include a first bitumen.
[0017] In this invention, the intermediate coke material obtained by sintering raw petroleum coke and calcined coke is mixed with the first bitumen, granulated and graphitized to obtain a graphite anode product. Its structure is a secondary particle, which binds the small particles together, and can take into account the expansion performance, capacity and compaction density. The first bitumen acts as a binder and has a high bonding strength.
[0018] Preferably, the raw materials for the graphite anode material further include raw coke graphite tailings powder and second pitch.
[0019] In this invention, after the intermediate coke and the first pitch are granulated, raw coke graphite tail powder and the second pitch can be added for further granulation, which can further improve the rate performance of the graphite anode material and make greater use of the application value of processing by-products, thereby reducing waste.
[0020] In a second aspect, the present invention provides a method for preparing a graphite anode material as described in the first aspect, the method comprising the following steps:
[0021] (1) Dynamically sinter the raw petroleum coke and the calcined coke to obtain intermediate coke;
[0022] (2) The intermediate coke described in step (1) is mixed with the first pitch, granulated, and graphitized to obtain the graphite anode material.
[0023] The preparation method provided by this invention, through the dynamic sintering process in step (1), can effectively avoid the agglomeration of raw coke during sintering, making the sintering more thorough and uniform. In terms of performance, the obtained graphite product can improve the capacity and compaction density of the material with less loss of rate performance. In terms of processing cost, it can shorten the calcination time and effectively improve the sintering capacity. Then, granulation and graphitization treatment can effectively improve the compaction of the graphite anode material and improve its electrochemical performance, especially the rate performance.
[0024] In this invention, without adding calcined coke during the preparation process, agglomeration will occur during sintering, affecting the consistency of the raw materials and ultimately impacting the material's capacity, yield, and recyclability. However, if calcined coke is added without dynamic sintering, the raw coke structure remains unchanged due to the absence of heat treatment conditions, and the raw material's capacity and compaction density do not significantly increase. Furthermore, dynamic sintering effectively disperses the raw materials. If static sintering is performed, the calcined coke cannot effectively isolate the raw coke components, similarly leading to agglomeration of the petroleum coke raw materials, affecting the consistency of the raw material structure, and ultimately impacting the material's capacity and compaction density.
[0025] Preferably, in step (1), based on the total mass of the raw coke and the calcined coke of the petroleum coke as 100%, the mass of the calcined coke is ≥5% and <10%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, etc.
[0026] Preferably, the dynamic sintering in step (1) is a stirring dynamic sintering.
[0027] The dynamic stirring sintering provided by this invention can effectively enable the development of mesophase structure in raw materials under dynamic and high-temperature conditions, for example, by using a vertical kettle for simultaneous stirring and sintering.
[0028] Preferably, the temperature of the stirring dynamic sintering is 500-650℃, such as 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃ or 650℃.
[0029] The stirring dynamic sintering temperature provided by this invention can affect the rate performance of the material if the temperature is too high, while it is not conducive to improving the material capacity and compaction density if the temperature is too low. That is, the sintering temperature of 500-650℃ provided by this invention achieves high capacity and synergistic realization of high capacity and compaction density.
[0030] Preferably, the stirring dynamic sintering time is 1 to 6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours.
[0031] In this invention, the addition of calcined coke can significantly reduce the sintering time, eliminating the need for excessively long sintering times. In fact, excessively long sintering times can negatively impact processing capacity and production costs.
[0032] Preferably, the stirring frequency of the dynamic sintering is 10 to 40 Hz, for example, 10 Hz, 15 Hz, 20 Hz, 25 Hz, 30 Hz, 35 Hz or 40 Hz.
[0033] In this invention, if the stirring frequency is too low, it will not be conducive to the full dispersion of raw material particles, while if the stirring frequency is too high, it will affect the power consumption and service life of the sintering equipment.
[0034] Preferably, before mixing in step (2), the intermediate coke is first pulverized to obtain intermediate coke micro powder with a D50 of 8 to 10 μm, such as 8 μm, 8.3 μm, 8.5 μm, 8.8 μm, 9 μm, 9.3 μm, 9.5 μm, 9.8 μm or 10 μm.
[0035] Preferably, based on the mass of the mixed substance described in step (2) as 100%, the amount of the first asphalt added is 10% to 30%, such as 10%, 13%, 15%, 18%, 20%, 13%, 25%, 28%, or 30%.
[0036] Preferably, the granulation temperature in step (2) is 400 to 600°C, such as 400°C, 430°C, 450°C, 480°C, 500°C, 530°C, 550°C, 580°C, or 600°C.
[0037] In this invention, if the temperature is too low when the intermediate coke and the first asphalt are granulated, the asphalt will not be fully coked, resulting in lower particle strength of the semi-finished product.
[0038] Preferably, the stirring frequency of the granulation in step (2) is 20 to 40 Hz, such as 20 Hz, 23 Hz, 25 Hz, 28 Hz, 30 Hz, 33 Hz, 35 Hz, 38 Hz or 40 Hz.
[0039] Preferably, the temperature of the graphitization process in step (2) is 2500 to 3100°C, such as 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C or 3100°C.
[0040] Preferably, the granulated particles from step (2) are subjected to heat treatment and then granulated again.
[0041] Preferably, the heat treatment temperature is 1000-1500℃, such as 1000℃, 1100℃, 1200℃, 1300℃, 1400℃ or 1500℃.
[0042] Preferably, the D50 of the heat-treated product is 12-16 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm.
[0043] Preferably, the regranulation process includes:
[0044] The heat-treated product is mixed with raw coke graphite tailings and second bitumen for regranulation.
[0045] In this invention, raw coke graphite tail powder and second asphalt can be added for regranulation. The second asphalt is used to bond the raw coke graphite tail powder to the surface of the heat-treated product to form a coating layer. Then, graphitization treatment is carried out, which can effectively improve the rate performance of the material. Moreover, a heat treatment process must be carried out before regranulation. If a heat treatment process is not carried out, the strength of the semi-finished particles from the first granulation will be low, and the particles will be broken up during the second granulation process.
[0046] Preferably, the raw coke graphite tail powder is subjected to a classification process to obtain raw coke graphite tail powder with a D50 of 3-8 μm, such as 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, and a specific surface area of 2-8 cm². 2 / g, for example, 2cm 2 / g, 3cm 2 / g、4cm 2 / g, 5cm 2 / g、6cm 2 / g、7cm 2 / g or 8cm 2 / g etc.
[0047] In this invention, by performing multiple grading processes on raw coke graphite tail powder to remove the extremely fine powder, the specific surface area of the tail powder can be reduced, its particle size distribution can be concentrated, and its performance in easy composite granulation can be improved. However, if the raw coke graphite tail powder is directly re-granulated, the tail powder cannot be completely attached to the surface of the primary granulated particles, and the resulting material has poor compaction density and ratio performance.
[0048] Preferably, the amount of raw coke graphite tail powder added is 2% to 10% of the product after heat treatment, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.
[0049] In this invention, if too much raw coke graphite tail powder is added, the tail powder will not be able to completely adhere to the surface of the primary granulation particles, resulting in too much free tail powder in the semi-finished product and a decrease in the compaction density of the material.
[0050] Preferably, the amount of the second asphalt added is 3 to 10% of the product after heat treatment in step (2), such as 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0051] Preferably, the D50 of the graphitized product after regranulation is 12-18 μm, for example 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm.
[0052] As a preferred technical solution, the preparation method includes the following steps:
[0053] (1) Petroleum coke raw coke and calcined coke are dynamically sintered at 500-650℃ for 1-6 hours with a stirring frequency of 10-40Hz to obtain intermediate coke;
[0054] (2) The intermediate coke described in step (1) is pulverized to obtain intermediate coke micro powder with a D50 of 8-10 μm. Then it is mixed with the first pitch and granulated at a stirring frequency of 20-40 Hz at 400-600℃. The mixture is then heat-treated at 1000-1500℃ to obtain a heat-treated product with a D50 of 12-16 μm. Then, raw coke graphite tail powder and the second pitch are added and mixed. The mixture is then granulated and graphitized at 2500-3100℃ to obtain the graphite anode material.
[0055] In step (1), the total mass of the raw coke and calcined coke is 100%, and the mass of the calcined coke is ≥5% and <10%; the mass of the mixed substance in step (2) is 100%, and the amount of asphalt added is 10-30%; the amount of raw coke graphite tail powder added is 2-10% of the heat-treated product; and the amount of the second asphalt added is 3-10% of the heat-treated product.
[0056] Thirdly, the present invention also provides a lithium-ion battery, the lithium-ion battery comprising the graphite anode material as described in the first aspect.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The graphite anode material provided by the present invention can ensure that the capacity and compaction density are improved while the rate performance loss is small.
[0059] (2) The preparation method provided by this invention, through the dynamic sintering process in step (1), can effectively avoid the agglomeration of raw coke during sintering, making the sintering more thorough and uniform. This results in a graphite product with minimal capacity loss, significantly improving the material's capacity and compaction density. It can also shorten the calcination time, effectively increasing sintering capacity. Further granulation and graphitization treatment can effectively enhance the capacity and compaction density of the graphite anode material. The anode sheet obtained from the graphite anode material provided by this invention has a compaction density of over 1.7 g / cc, while the battery provided by this invention has a discharge capacity of over 349.3 mAh / g at 0.1C and a rate performance of over 73.3% at 2C / 0.2C. Attached Figure Description
[0060] Figure 1 This is a SEM image of the intermediate focal point provided in Embodiment 1 of this application.
[0061] Figure 2 This is a SEM image of the coke provided in Embodiment 1 of this application.
[0062] Figure 3 This is a SEM image of the calcined coke provided in Example 1 of this application.
[0063] Figure 4 This is a SEM image of the graphite anode material provided in Embodiment 1 of this application. Detailed Implementation
[0064] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0065] Example 1
[0066] This embodiment provides a method for preparing a graphite anode material, the method being as follows:
[0067] (1) The raw petroleum coke is crushed into particles smaller than 10 mm using a jaw crusher and mixed with calcined coke (calcined coke accounts for 5% of the mixed material) (both raw petroleum coke and calcined coke are purchased directly from Sinopec's refinery, and the particle size of calcined coke is smaller than that of raw petroleum coke). Then, the mixture is dynamically sintered at 500°C for 6 hours in a vertical kettle (stirring frequency 25 Hz) to obtain intermediate coke particles.
[0068] (2) The intermediate coke particles are pulverized to obtain particles with a D50 of 9μm. Then, asphalt (high temperature binder asphalt with a softening point of 250℃ and QI≤5%) is added and mixed. The mixture is granulated at 450℃ and 30Hz stirring frequency, and then heat-treated at 1000℃ to obtain a heat-treated product with a D50 of 13μm.
[0069] (3) The raw coke graphite tail powder (after classification treatment, the D50 is 5μm and the specific surface area is 4.5cm²) 2 / g) and the second asphalt (low-temperature asphalt with a softening point of 90℃ and QI≤5%) (the amount of raw coke graphite tail powder added is 5% of the heat-treated product, and the asphalt is 4% of the heat-treated product) are re-granulated at a temperature of 400℃, and finally graphitized at 3000℃ to obtain the graphite anode material.
[0070] Figure 1 This diagram illustrates the polarization structure of the intermediate focal point provided in Embodiment 1 of this application. Figure 2 The diagram shows the polarizing structure of the focal plane provided in Embodiment 1 of this application. Figure 3 The diagram shows the polarization structure of the calcined coke provided in Embodiment 1 of this application. Figures 1-3 It can be seen that, Figure 2 Meso-coke has a smaller fiber structure size, poorer fiber orientation, and a certain degree of domain structure; while Figure 3 The structure of the raw materials is basically composed entirely of long, thin fibers, with large fiber structure size and excellent orientation. Figure 2 The structure of intermediate coke raw materials lies between the former two. In raw coke, the granular structure transforms into a fibrous structure, with larger fiber size and better orientation, but it does not reach the level of calcined coke. Its polarization structure characteristics are between those of raw coke and calcined coke.
[0071] Figure 4 The SEM image of the graphite anode material provided in Embodiment 1 of this application is shown. Figure 4 It can be seen that the negative electrode material provided by the present invention has good particle uniformity, with several small particles sticking together, very few extremely large particles and free single particles, and a high degree of composite of secondary particles.
[0072] Example 2
[0073] This embodiment provides a method for preparing a graphite anode material, the method being as follows:
[0074] (1) The raw petroleum coke is crushed into particles smaller than 10 mm using a jaw crusher, and mixed with calcined coke (calcined coke accounts for 8% of the mixed material, and the particle size of calcined coke is less than that of raw petroleum coke). Then, it is stirred and dynamically sintered in a vertical kettle at a temperature of 580°C for 4 hours (stirring frequency 40 Hz) to obtain intermediate coke particles.
[0075] (2) The intermediate coke particles are pulverized to obtain particles with a D50 of 8μm. Then, asphalt (high temperature binder asphalt with a softening point of 250℃ and QI≤5%) is added and mixed. The mixture is granulated at 600℃ and 30Hz stirring frequency, and then heat-treated at 1300℃ to obtain a heat-treated product with a diameter of 15μm.
[0076] (3) The raw coke graphite tail powder (after grading, the D50 is 8μm and the specific surface area is 2cm²) 2 The graphite anode material is obtained by re-granulation of the graphite tail powder (2% of the heat-treated product and 3% of the graphite tail powder) and the second asphalt (low-temperature asphalt with a softening point of 90℃ and QI≤5%) (the amount of raw coke graphite tail powder added is 2% of the heat-treated product and the asphalt is 3% of the heat-treated product) at a re-granulation temperature of 400℃, and finally graphitized at 2900℃.
[0077] Example 3
[0078] This embodiment provides a method for preparing a graphite anode material, the method being as follows:
[0079] (1) The raw petroleum coke is crushed into particles smaller than 10 mm using a jaw crusher, and mixed with calcined coke (calcined coke accounts for 9.5% of the mixed material, and the particle size of calcined coke is consistent with that of raw petroleum coke). Then, it is dynamically sintered in a vertical kettle at a temperature of 650°C for 1 hour (stirring frequency 10 Hz) to obtain intermediate coke particles.
[0080] (2) The intermediate coke particles are pulverized to obtain particles with a D50 of 8μm. Then, asphalt (high temperature binder asphalt with a softening point of 250℃ and QI≤5%) is added and mixed. The mixture is granulated at 560℃ and 30Hz stirring frequency, and then heat-treated at 1300℃ to obtain a heat-treated product with a diameter of 15μm.
[0081] (3) The raw coke graphite tail powder (after classification treatment, the D50 is 3μm and the specific surface area is 8cm²) 2 / g) and the second asphalt (low-temperature asphalt with a softening point of 90℃ and QI≤5%) (the amount of raw coke graphite tail powder added is 10% of the heat-treated product, and the asphalt is 10% of the heat-treated product) are re-granulated at a temperature of 400℃, and finally graphitized at 2900℃ to obtain the graphite anode material.
[0082] Example 4
[0083] The difference between this embodiment and embodiment 1 is that step (3) is not performed in this embodiment. After granulation in step (2), graphitization treatment at 3000℃ is performed directly to obtain the graphite anode material.
[0084] The remaining preparation methods and parameters are consistent with those in Example 1.
[0085] Example 5
[0086] The difference between this embodiment and embodiment 1 is that the amount of calcined coke added in step (1) of this embodiment is 4%.
[0087] The remaining preparation methods and parameters are consistent with those in Example 1.
[0088] Example 6
[0089] The difference between this embodiment and Embodiment 1 is that the amount of calcined coke added in step (1) of this embodiment is 13%.
[0090] The remaining preparation methods and parameters are consistent with those in Example 1.
[0091] Example 7
[0092] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (1) of this embodiment is 450℃.
[0093] The remaining preparation methods and parameters are consistent with those in Example 1.
[0094] Example 8
[0095] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (1) of this embodiment is 700℃.
[0096] The remaining preparation methods and parameters are consistent with those in Example 1.
[0097] Example 9
[0098] The difference between this embodiment and embodiment 1 is that the stirring frequency in step (1) of this embodiment is 50Hz.
[0099] The remaining preparation methods and parameters are consistent with those in Example 1.
[0100] Example 10
[0101] The difference between this embodiment and embodiment 1 is that in step (3) of this embodiment, the raw coke graphite tail powder is not graded and is used directly.
[0102] The remaining preparation methods and parameters are consistent with those in Example 1. Comparative Example 1
[0103] The difference between this comparative example and Example 1 is that calcined coke is not added in step (1) of this comparative example.
[0104] The remaining preparation methods and parameters are consistent with those in Example 1.
[0105] Comparative Example 2
[0106] The difference between this comparative example and Example 1 is that dynamic sintering is not performed in step (1) of this comparative example.
[0107] The remaining preparation methods and parameters are consistent with those in Example 1.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 1 is that in step (1) of this comparative example, dynamic sintering is replaced by static sintering, that is, sintering is carried out directly in the sintering furnace.
[0110] The remaining preparation methods and parameters are consistent with those in Example 1.
[0111] The graphite anode materials provided in Examples 1-10 and Comparative Examples 1-3 were used as anode active materials. They were mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:3:2. Water was added to obtain anode slurry, which was coated on the surface of copper foil, dried and rolled to obtain anode sheet. A coin cell was obtained by using a lithium sheet as counter electrode.
[0112] The coin cells obtained above were subjected to electrochemical performance testing under the following conditions: constant current charge and discharge at room temperature, with a charge and discharge cutoff voltage of 0.01V-1.5V. The results are shown in Table 1.
[0113] Table 1
[0114]
[0115] The data from Examples 1 and 4 show that high capacity / high compaction was achieved without regranulation, but the rate performance was slightly reduced.
[0116] The data from Examples 1, 5, and 6 show that if the amount of calcined coke added is too small, the capacity and rate performance will decrease, while if the amount added is too large, the rate performance will be severely affected.
[0117] The data results from Examples 1, 7 and 8 show that if the sintering temperature in step (1) is too low, the capacity and compaction cannot be effectively improved, while if the sintering temperature is too high, the rate performance will be affected.
[0118] The data results from Examples 1 and 9 show that the high stirring frequency during the sintering process in step (1) did not have a substantial impact on the material properties, but it did increase the power consumption of the equipment.
[0119] The data results from Examples 1 and 10 show that the lack of grading treatment for raw coke graphite tail powder leads to a decrease in compaction and a severe decrease in rate performance.
[0120] The data from Example 1 and Comparative Example 1 show that without the addition of calcined coke, the consistency of the dynamic sintering treatment effect is poor. Some of the raw coke is fully sintered to obtain intermediate coke, while some of the raw coke is not fully sintered and is still in a near-original state. Therefore, the overall performance of the intermediate coke cannot be fully utilized, and its capacity and compaction density are low, resulting in poor rate performance.
[0121] The data from Example 1 and Comparative Example 2 show that without dynamic sintering after adding calcined coke, the raw coke component in the raw material mixture cannot be fully converted, intermediate coke is not obtained, and the capacity and compaction of the final product will not be significantly improved.
[0122] The data from Example 1 and Comparative Example 3 show that after the dynamic sintering was changed to static sintering, even with the addition of calcined coke, the sintering effect was not uniform due to the lack of external force for dispersion. Some of the raw coke was not fully sintered and remained in a near-original state. Therefore, the overall performance of the intermediate coke could not be fully utilized, and its capacity and compaction density were low, resulting in poor rate performance, which would seriously affect the capacity, compaction and rate performance of the material.
[0123] In summary, by incorporating calcined coke into the dynamic sintering process, agglomeration of raw coke during sintering can be effectively avoided, resulting in more thorough and uniform sintering. This leads to improved material capacity and compaction density in the obtained graphite product while minimizing rate performance loss, and also shortens sintering time, effectively increasing sintering capacity. The negative electrode sheet obtained from the graphite negative electrode material provided by this invention can achieve a compaction density of over 1.7 g / cc, while the battery provided by this invention can achieve a discharge capacity of over 349.3 mAh / g at 0.1C and a rate performance of over 73.3% at 2C / 0.2C.
[0124] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a graphite anode material, characterized in that, The preparation method includes the following steps: (1) Dynamically sinter the raw petroleum coke and the calcined coke to obtain intermediate coke; (2) The intermediate coke described in step (1) is mixed with the first pitch, granulated, and graphitized to obtain the graphite anode material; The particle size of the calcined coke in step (1) is ≤ the particle size of the raw petroleum coke; With the total mass of the raw petroleum coke and the calcined coke as 100%, the mass of the calcined coke is ≥5% and <10%.
2. The method for preparing the graphite anode material according to claim 1, characterized in that, The dynamic sintering in step (1) is stirring dynamic sintering.
3. The method for preparing the graphite anode material according to claim 2, characterized in that, The temperature for the dynamic stirring sintering is 500~650℃.
4. The method for preparing the graphite anode material according to claim 2, characterized in that, The stirring dynamic sintering time is 1~6h.
5. The method for preparing the graphite anode material according to claim 2, characterized in that, The stirring frequency for the dynamic stirring sintering is 10~40Hz.
6. The method for preparing the graphite anode material according to claim 1, characterized in that, Before mixing in step (2), the intermediate coke is first crushed to obtain intermediate coke micro powder with a D50 of 8~10μm.
7. The method for preparing the graphite anode material according to claim 1, characterized in that, Based on the mass of the mixed substance described in step (2) as 100%, the amount of the first asphalt added is 10~30%.
8. The method for preparing the graphite anode material according to claim 1, characterized in that, The granulation temperature in step (2) is 400~600℃.
9. The method for preparing the graphite anode material according to claim 1, characterized in that, The stirring frequency for granulation in step (2) is 20~40Hz.
10. The method for preparing the graphite anode material according to claim 1, characterized in that, The temperature of the graphitization process in step (2) is 2500~3100℃.
11. The method for preparing the graphite anode material according to claim 1, characterized in that, The granulated particles from step (2) are subjected to heat treatment and then granulated again.
12. The method for preparing the graphite anode material according to claim 11, characterized in that, The heat treatment temperature is 1000~1500℃.
13. The method for preparing the graphite anode material according to claim 11, characterized in that, The D50 of the heat-treated product is 12~16μm.
14. The method for preparing the graphite anode material according to claim 11, characterized in that, The regranulation process includes: The heat-treated product is mixed with raw coke graphite tailings and second pitch for regranulation.
15. The method for preparing the graphite anode material according to claim 14, characterized in that, The raw coke graphite tail powder was graded to obtain raw coke graphite tail powder with a D50 of 3~8μm and a specific surface area of 2~8cm². 2 / g.
16. The method for preparing the graphite anode material according to claim 14, characterized in that, The amount of raw coke graphite tail powder added is 2-10% of the product after heat treatment.
17. The method for preparing the graphite anode material according to claim 14, characterized in that, The amount of the second bitumen added is 3 to 10% of the product after heat treatment in step (2).
18. The method for preparing the graphite anode material according to claim 14, characterized in that, After regranulation, the D50 of the graphitized product is 12~18μm.
19. The method for preparing the graphite anode material according to claim 1, characterized in that, The preparation method includes the following steps: (1) Petroleum coke raw coke and calcined coke are dynamically sintered at 500-650℃ for 1-6 hours with a stirring frequency of 10-40Hz to obtain intermediate coke; (2) The intermediate coke described in step (1) is crushed to obtain intermediate coke micro powder with a D50 of 8~10μm, and then mixed with the first pitch. Granulation is carried out at 400~600℃ with a stirring frequency of 20~40Hz, and heat treatment is carried out at 1000~1500℃ to obtain a heat-treated product with a D50 of 12~16μm. Then, raw coke graphite tail powder and the second pitch are added and mixed, granulated again, and graphitized at 2500~3100℃ to obtain the graphite anode material. Wherein, taking the mass of the mixed substance in step (2) as 100%, the amount of asphalt added is 10~30%; the amount of raw coke graphite tail powder added is 2~10% of the heat-treated product; and the amount of the second asphalt added is 3~10% of the heat-treated product.
20. A lithium-ion battery, characterized in that, The lithium-ion battery includes a graphite anode material prepared by the preparation method according to any one of claims 1 to 19.
Citation Information
Patent Citations
Rapidly-charged graphite lithium ion battery anode material and preparation method thereof
CN105024043A
Porous secondary particle negative electrode material for lithium ion battery, and preparation method thereof
CN111628170A
Method for producing lithium ion battery negative electrode material by asphalt secondary coating process
CN109473678A
Manufacturing method of battery negative electrode material based on raw needle coke and calcined coke
CN110718690A
Modified natural graphite negative electrode material for power battery and preparation method of modified natural graphite negative electrode material
CN113422023A
